2018
DOI: 10.1371/journal.pone.0206647
|View full text |Cite
|
Sign up to set email alerts
|

A survey on adolescent health information seeking behavior related to high-risk behaviors in a selected educational district in Isfahan

Abstract: BackgroundsThe characteristics and conditions of growth and development have made adolescence one of the most vital and influential ages for prevention and health promotion, especially in the area of high-risk behaviors. Accordingly, the aim of this study was to determine adolescent health information seeking behavior related to high-risk behaviors in a selected educational district in Isfahan (Iran).MethodologyThe present study was of an applied type, which was conducted using the survey research method. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(65 citation statements)
references
References 15 publications
1
44
0
5
Order By: Relevance
“…In discussion, these explanations are discussed and suggestions are provided. requires providing appropriate and complete health information for them [27]. Health information includes a range of information that can be used in personal and community health decisions [28].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In discussion, these explanations are discussed and suggestions are provided. requires providing appropriate and complete health information for them [27]. Health information includes a range of information that can be used in personal and community health decisions [28].…”
Section: Resultsmentioning
confidence: 99%
“…This can have many explanations. Challenges such as the lack of appropriate information and inadequate quality, poor health literacy of internet users, insufficient skills in searching information, lack of trust in online health information sources and concerns about the security and confidentiality reduce the potential of internet in serving the health of population [27,33,44]. The production and dissemination of health misinformation is also a serious concern.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Esmaeilzadeh et al (2018) reported the scourge of alcohol and drug abuse and illicit sexual practices among Iranian youths which has caused a decline in the health condition of young people in the country. This awareness has caused youths to seek health information to improve their health status.…”
Section: Description Of Study 21 Statement Of the Problemmentioning
confidence: 99%
“…More importantly, health information is considered very essential for youths who make up a substantial part of the world's population. According to Esmaeilzadeh, Ashrafi-rizi, Shahrzadi, & Mostafavi (2018), a fifth of the world's population is between 10 and 19 years old and 85% of them live in developing countries. Provision of health information for young people is fundamental to national development.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation